Biological variation of extracellular matrix biomarkers in patients with stable chronic heart failure - Täger, Tobias; Fröhlich, Hanna; Corletto, Anna; Katus, Hugo; Frankenstein, Lutz (Clinical research in cardiology, 2017)
BackgroundExtracellular matrix (ECM) biomarkers such as matrix metalloproteinases (MMPs) and their inhibitors (TIMPs) are pathophysiological key, prognostic marker and therapeutic target in chronic heart failure (HF). Serial measurements of MMPs and TIMPs may be useful for guidance of these applications. However, interpretation of time-dependent changes requires knowledge about the biological variation of ECM biomarkers.MethodsWe performed measurements of MMP-2, MMP-9, TIMP-1, and TIMP-4 in 50 patients with chronic HF who met rigid criteria for clinical stability at 3-h, 6-h, 1-week and 2-week time intervals. In addition, clinical and haemodynamic assessment was performed at baseline, at 1- and 2-week intervals. Haemodynamic variables were measured using inert gas rebreathing and impedance cardiography. Heart rhythm was monitored with external ECG event recorders throughout the complete study. Reference change values (RCVs) and minimal important differences (MIDs) were determined for MMP-2, MMP-9, TIMP-1, and TIMP-4.ResultsClinical and haemodynamic variables were stable over time. Depending on the time-interval, RCVs ranged between 4.9 and 11.7% for MMP-2, 26.4 and 56.7% for MMP-9, 10.8 and 30.7% for TIMP-1, and 16.0 and 47.4% for TIMP-4, respectively. The MIDs varied between 43.38 and 65.22 ng/ml for MMP-2, 28.71 and 40.96 ng/ml for MMP-9, 52.32 and 156.07 ng/ml for TIMP-1, and 293.92 and 798.04 pg/ml for TIMP-4, respectively.ConclusionThe biological variation of ECM biomarkers differs with respect to individual biomarkers and time intervals. MMP-2 may be most suitable for serial biomarker measurements, as the biological variation is low irrespective of the time interval between measurements.
Published online: 4 August 2017
Gesehen am 25.06.2018